Peripheral blood CD19 positive B lymphocytes increase after ischemic stroke and correlate with carotid atherosclerosis - Zhang, Yuhua; Jiang, Yu; Zou, Yutian; Fan, Yinyin; Feng, Ping; Fu, Xiang; Li, Keru; Zhang, Jinru; Dong, Yunlei; Yan, Shuying; Zhang, Yanlin (Frontiers in Neurology, 2023)
Atherosclerosis is the primary pathological basis of ischemic stroke, and dyslipidemia is one of its major etiological factors. Acute ischemic stroke patients exhibit imbalances in lymphocyte subpopulations, yet the correlation between these dynamic changes in lymphocyte subpopulations and lipid metabolism disorders, as well as carotid atherosclerosis in stroke patients remains poorly understood. We retrospectively analyzed the demographic data, risk factors of cerebrovascular disease, laboratory examination (lymphocyte subsets, lipid indexes, etc.), clinical features and carotid artery ultrasound results of patients with acute ischemic stroke admitted to the Department of Neurology of the Second Affiliated Hospital of Soochow University from December 2017 to September 2019 and non-stroke patients with dizziness/vertigo during the same period. The results showed that peripheral B lymphocyte proportions are elevated in acute ischemic stroke patients compared with those of the control group (13.6±5.3 vs. 11.7±4.4%, P=0.006). Higher B lymphocyte proportions are associated with concurrent dyslipidemia, increased levels of vascular risk factors including triglycerides (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and very-low-density lipoprotein cholesterol (VLDL-C), as well as decreased levels of the protective factor high-density lipoprotein cholesterol (HDL-C). Elevated B lymphocyte proportions are independently correlated with carotid atherosclerosis in stroke patients.